Implementasi Manajemen Pembiayaan di MTs An-Nawawi 01 Berjan Purworejo - Muhlil Musolin; Khoirun Nisa’; Laelatul Mudmiroh (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2021)
Education funding is one of the central systems in education, financing is part of the support of the implementation of education because it involves the operational financing of education implementation from the smallest to the largest operational funding. This research discusses the implementation of financing management in An Nawawi 01 Berjan Purworejo MTs. This study uses a qualitative descriptive approach and data collection techniques used are observation, interviews with employees of the treasurer of the madrasa and documentation related to financial records at An-Nawawi 01 MTs Berjan Purworejo. Data creatiability test is done by using triangulation, data dependability test, transfermability test and confirmability test. Data analysis techniques using qualitative descriptive analysis techniques with stages of data collection, data reduction, data presentation, to drawing conclusions. The results showed that the implementation of financial management in MTs An-Nawawi 01 Berjan Purworejo began with financial planning (budgeting) through the process of financial budgeting that was carried out in accordance with stages systematically. Execution / accounting (accounting) with accounting books is general cash books, invoices, cash assistance books, salary receipt books, bank supporting books and financial statements. The financial supervision process begins by making the RAPBM the standard for overseeing the implementation of supervision both internal and external.